Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Aparatur Sipil Negara pada Sekretariat Dewan Perwakilan Rakyat Kota (DPRK) Subulussalam - Pratama, Tio Harry; Purba, Amir; Kusmanto, Heri (Mahesa Research Center, 2022)
This study aims to determine the effect of work discipline and work motivation on the performance of ASN at the Secretariat of DPRK Subulussalam. The hypothesis proposed is that work discipline and work motivation have a significant effect on the performance of ASN at the DPRK Subulussalam Secretariat. The variables studied consisted of work discipline and work motivation as independent variables and performance as the dependent variable. The method of collecting data is by means of a list of questions. Method of data analysis using multiple linear regression method. The results showed that work discipline had a positive and significant effect on the performance of the ASN Secretariat of DPRK Subulussalam. The better the employee's work discipline, the higher the performanceThe variables of work discipline and work motivation together have a significant effect on the performance of the ASN Secretariat of DPRK Subulussalam. Variations in employee performance can be explained by work discipline and motivation of 95.00%, while the remaining 5.00% is explained by other factors, such as communication, leadership and other factors that are not explained in this research model.